An introduction to randomized evaluations and its application in agricultural economics - A G Adeeth Cariappa (Agricultural Economics Research Review, 2023)
Large-scale randomized evaluations or randomized control trials (RCT) are useful in evidencebased policymaking, but these are seldom used by agricultural economists in India. This paper discusses in detail the application of RCTs—from agricultural technology adoption to nudging farmers to price sensitivity. It is necessary to estimate the sample size, level, and type of randomization to design and implement a randomized evaluation properly. Agricultural economists at various institutes can collaborate in conducting large-scale RCTs and evaluate the effect of interventions in different contexts. The paper also lists potential applications for RCTs in agriculture.